New York 2140 - Robinson, Kim Stanley 1952- (Orbit, 2018)
"A new vision of the future from Kim Stanley Robinson, the New York Times bestselling author of science fiction masterworks such as the Mars trilogy, 2312, and Aurora. The waters rose, submerging New York City. But the residents adapted and it remained the bustling, vibrant metropolis it had always been. Though changed forever. Every street became a canal. Every skyscraper an island. Through the eyes of the varied inhabitants of one building Kim Stanley Robinson shows us how one of our great cities will change with the rising tides. And how we too will change"...
Keywords: Science fiction / gsafd; FICTION / Science Fiction / Space Opera / bisacsh; FICTION / Science Fiction / High Tech / bisacsh; FICTION / Science Fiction / Adventure / bisacsh; Twenty-second century -- Fiction; Interpersonal relations -- Fiction; FICTION / Science Fiction / Space Opera; FICTION / Science Fiction / High Tech; FICTION / Science Fiction / Adventure; New York (State) -- Fiction; Fiktionale Darstellung